2015
DOI: 10.1007/s10578-015-0557-8
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-Wake Patterns of Adolescents with Borderline Personality Disorder and Bipolar Disorder

Abstract: Sleep-wake patterns are rarely examined in adolescents with borderline personality disorder (BPD) or bipolar disorder (BD). Within a developmental perspective, this study explores the sleep-wake cycle of adolescents aged 12-17 years with BPD or BD and healthy controls (HC) during periods with and without entrainment by school/work schedules. Eighteen euthymic BPD, six euthymic BD, and 20 HC adolescents wore wrist actigraphy during nine consecutive days to assess sleep-wake patterns. During school/work days, BP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 89 publications
3
29
2
Order By: Relevance
“…Nearly all studies examining objective sleep measures used polysomnography in laboratory conditions. One study utilised a portable electroencephalogram sleep recording device (Hornung et al, 2008), while two utilised wrist actigraphy (Bromundt et al, 2013;Huỳnh, Guilé, Breton, & Godbout, 2015).…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nearly all studies examining objective sleep measures used polysomnography in laboratory conditions. One study utilised a portable electroencephalogram sleep recording device (Hornung et al, 2008), while two utilised wrist actigraphy (Bromundt et al, 2013;Huỳnh, Guilé, Breton, & Godbout, 2015).…”
Section: Search Resultsmentioning
confidence: 99%
“…Most studies with clinical control groups included depressed patients with the exception of one group of prisoners with Antisocial Personality Disorder (Lindberg et al, 2003), one group of patients with insomnia (Bastien et al, 2008), and one group of adolescent outpatients with bipolar disorder (Huỳnh et al, 2015). Most studies reported a psychotropic medication wash-out period (usually of 2 weeks) prior to sleep assessment; five did not report a wash-out period (Huỳnh et al, 2015;Plante, Frankenburg, Fitzmaurice, & Zanarini, 2013b;Selby et al, 2013;Simor, Csóka, & Bódizs, 2010;Taherifard, Abolghasemi, & Hajloo, 2015).…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations